Evaluation of eating and rumination behaviour using a noseband pressure sensor in cows during the peripartum period - Braun, Ueli (BioMed Central, 2014)
BACKGROUND: Eating and rumination variables were recorded in ten healthy cows over 5 days (group A) to generate reference intervals for comparison with the same variables recorded in ten cows in advanced pregnancy from ten days prepartum to ten days postpartum (group B). A pressure sensor integrated into the noseband of a halter recorded individual chewing movements. The endpoints calculated on a daily basis for each cow included duration of eating and rumination, number of eating and rumination phases, number of chewing cycles during eating and rumination, number of regurgitated cuds and number of chewing cycles per cud. RESULTS: The following reference intervals were established in the cows of group A: duration of eating, 212 to 394 min; number of chewing cycles during eating 13‘101 to 26‘515; number of eating phases 10 to 24; duration of rumination 304 to 471 min; number of regurgitated cuds 366 to 611; number of chewing cycles per cud 53 to 57; and number of rumination phases 9 to 18. In the cows of group B, duration of eating was 186 min and below the normal range ten days prepartum and decreased to 114 min on the day of calving, after which time it increased significantly to 266 min by day 10. The number of chewing cycles during eating had the same profile as duration of eating. Duration of rumination was in the normal range except for the day of parturition. It varied from 329 to 391 min prepartum, decreased significantly to 214 min on the day of parturition and then more than doubled by day 10. The number of regurgitated cuds had a profile similar to the duration of rumination. The number of chewing cycles per cud was lowest on the day before and the day of parturition and ranged from 45 to 61. CONCLUSIONS: This study showed that eating and rumination variables decrease from ten days before parturition to a minimum on the day of parturition, after which time they increase.